Thermodynamic and Theoretical Studies of some N-substituted phthalimides Derivatives (Journal of the College of Basic Education, 2023)
N,N’-(biphenyl)bisphthalimide and N-(4’-amino __ biphenyl)phthalimide were chosen in this study to compare the stabilitytheoretically by density function theory (DFT) using B3LYP/6-31Gmethod, the electronic properties of these imides indicate that compound(N,N’-(biphenyl)bisphthalimide) is more stable than the compound (N-(4’-aminobiphenyl) phthalimide) by (-0.8422 eV or -19.4215 Keal.mo!'')depending on the values of HOMO, synthesis _ reaction of imide isspontaneous and endothermic at temperature 150°C according to the valuesof A,S, A,G and A,H thermodynamically.INTRODUCTION Imides are organic compounds for N-monoacy] derivatives of amidewhich may be open or cyclic chain. Cyclic imide constitute an importantclass of compounds possessing bis-amide linkage with common nitrogen.Imide very important molecules because their activity as antibacterial,antifungal, anti nociceptive, anticonvulsant and antitumor!, They havebeen useful building blocks in the synthesis of natural products’! and otherheterocycles as well!*!, Their ability to cross biological membranes in-vivo,due to their hydrophobicity is well established'“!,The preparation of imideshas received considerable attention during recent year A number ofmethods such as acylation of amides with acyl chlorides, anhydrides andcarboxylic esters or acids), amino carbonylation of aryl bromides'*! havebeen reported for the preparation of acyclic imides.COMPUTATIONAL METHODS Molecular geometries of the all molecules were fully optimized withthe hybrid density functional theory (DFT) B3LYP method!”"'"! using the6-31G basis set!!?!3! by means of the Gaussian 09, revision A.02!"4! usedfor all geometry optimizitions, thermodynamic functions at conditions